P‐12.15: An evaluation method of photo‐alignment PI for vehicle TFT‐LCD panel. (26th August 2021) - Zhao, Yujie; Zhang, Jingsi; Zhang, Xiaona; Wan, Nianqing; Jiang, Jinqiang; Tang, Rong; Chen, Xiangyu; Song, Di
Abstract : As the increasing requirements of vehicle panel specifications, traditional PI materials can not meet the optical and yield requirements of vehicle panel, A new type of PI is urgently needed to improve the optical performance and yield of vehicle panel. Compared with the traditional rubbing PI material, photo‐alignment PI material has the advantages like wide viewing angle, high contrast, less particles, less ESD and so on(Refer to table 1). In summary it can effectively improve the optical performance and yield of the panel. Through the analysis of PI material structure and the summary a large number of experimental data, we completed the PI type selection and input. Finally, a new type of PI material was selected and successfully put into the mass production of vehicle TFT‐LCD.